ATP modulation of mitogen activated protein kinases and intracellular Ca2+ in breast cancer (MCF-7) cells - Scodelaro Bilbao, Paola Gabriela (2007)
In the breast tumor cell line MCF-7, extracellular nucleotides induce transient elevations in intracellular calcium concentration ([Ca2+]i). In this study we show that stimulation with ATP or UTP sensitizes MCF-7 cells to mechanical stress leading to an additional transient Ca2+ influx. ATP ⩾ ATPγ-S ⩾ UTP >>> ADP = ADPβ-S elevate [Ca2+]i, proving the presence of P2Y2/P2Y4 purinergic receptor subtypes. In addition, cell stimulation with ATP, ATPγ-S or UTP but not ADPβ-S induced the phosphorylation of ERK1/2, p38 and JNK1/2 mitogen activated protein kinases (MAPKs). The use of Gd3+, La3+ or a Ca2+-free medium, inhibited ATP-dependent stress activated Ca2+ (SAC) influx, but had no effect on MAPK phosphorylation. ATP-induced activation of MAPKs was diminished by two PI-PLC inhibitors and an IP3 receptor antagonist. These results evidence an ATP-sensitive SAC influx in MCF-7 cells and indicate that phosphorylation of MAPKs by ATP is dependent on PI-PLC/IP3/Ca2+i release but independent of SAC influx in these cells, differently to other cell types.